Engineering Characteristics at Early Age of Cemented Silica Fume Paste for Peat Compaction Grouting - Alsidqi, Hasan; Lolom Evalita, Hutabarat (Bentham Open, 2024)
Abstract: Introduction: Cemented Silica Fume Paste (CSFP) is currently being investigated for compaction grouting material to improve peat ground engineering properties. The CSFP is made in the laboratory using a proportional mixture of silica fume, cement binder, and tap water. The silica fume material is a byproduct of the metal processing industry, which critically requires a better alternative utilization in the near future in order to cut the storage cost and minimize the environmental impact. Aims: This paper aims to present preliminary results on the engineering characteristics of CSFP at an early age through a series of rheological and strength tests. A general observation of the physical properties and microstructure of CSFP is also presented. Methods: The CSFP specimens with cement binder range from 0% to 30% with the increment of 5% and Water-to- Solid (W/S) ratio ranges from 0.8, 0.9 and 1.0 were prepared and tested. A series of rheology test and Unconfined Compressive Strength (UCS) tests were carried out for the CSFP specimens at an early age. The data were analyzed statistically and mathematical formulation is presented. Results: The results indicate that CSFP mixtures behave as pseudoplastic or shear thinning fluid, where the shear stress and viscosity depend highly on the shear rates. The higher the shear rates, the higher the shear stress and the lower the viscosity. Curve fitting showed that the best relationship between shear stress and shear rate is the power law function (Ostwald–de Waele relationship). Statistical parameters, k, n, R2 of the power law functions are reported. There was no good correlation found between the power law function statistical parameters and the cement content. The UCS tests showed that the shear strength increases with the amount of cement content. The actual W/S reduces as the cement content increases, which is attributed to the cement hydration. Conclusion: The CSFP mixtures were found to be a pseudoplastic or shear thinning fluid at an early age that provides an advantage during the material injection on the ground. Cemented Silica Fume Paste can be potentially used as compaction grout to improve peat. The current findings provide a better understanding of the CSFP characteristics and to better design CSFP to be injected into peat ground. Keywords: Cemented silica fume paste, Rheology, Strength, Peat, Compaction grouting, Pseudoplastic.